Criteria of evaluating multimedia presentations produced in English by students of engineering and technical specialties - Kryvonos, Iryna; Кривонос, Ірина Анатоліївна; Кривонос, Ирина Анатольевна (My University, 2017)
EN: The article is devoted to the problem of evaluating the formation of skills and abilities of producing a presentation in English by students of engineering and technical specialties. The criteria for evaluation are defined and described. Key words: a multimedia presentation in English, evaluating of formation of skills and abilities, students of engineering and technical specialties.
Keywords: a multimedia presentation in English; evaluating of formation of skills and abilities; students of engineering and technical specialties